Improvement of gut-vascular barrier by terlipressin reduces bacterial translocation and remote organ injuries in gut-derived sepsis - Chang, Zenan; Zhang, Yinan; Lin, Ming; Wen, Shihong; Lai, Hanjin; Zhan, Yaqing; Zhu, Xiufen; Huang, Zhikun; Zhang, Xuyu; Liu, Zimeng (Frontiers in Pharmacology, 2022)
Gut-vascular barrier (GVB) serves as the last barrier to limit the migration of intestinal toxins into the blood circulation. The efficacy of terlipressin (a vasopressin V1 receptor agonist) in reducing GVB and multiple organ damage in gut-derived sepsis is unknown. In this study, we hypothesized that, besides other intestinal barriers, GVB play a key role in gut-derived sepsis and terlipressin improve GVB damage and then reduce bacterial translocation and organ injuries. We examined the change of GVB, the translocation of intestinal bacteria and macromolecules, and the impairments of multiple organs after sepsis attack in vivo and vitro, and explored the potential signaling related to the protective effect of terlipressin. Terlipressin significantly improved GVB damage and reduced translocation of intestinal macromolecules and bacteria by activating phosphoinositide 3-kinase (PI3K) signaling. Of note, intestinal plasmalemma vesicle-associated protein-1(PV-1) expression was significantly correlated with translocation of macromolecules, and dramatic increase of macromolecules was observed in intestinal tissues whereas fewer macromolecules and bacteria were observed in blood, liver and lung following terlipressin treatment. In vitro, terlipressin restored transendothelial electrical resistance (TER) during interleukin-1β stimulation and small interfering RNA targeting β-catenin transfection blocked the change of TER delivered by terlipressin. Collectively, terlipressin alleviated GVB damage and subsequent bacterial translocation via blood vessels after sepsis challenge, resulting in reduced distant organ injuries. The responsible mechanisms may involve the activation of PI3K/β-catenin pathway.